2022
DOI: 10.3389/fnagi.2022.996217
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib in Parkinson's disease: A systematic review and meta-analysis

Abstract: BackgroundNilotinib, which inhibits cellular Abelson tyrosine kinase, may be an effective treatment for patients with Parkinson's disease (PD). The purpose of this study is to evaluate the outcomes of different doses of nilotinib in patients with PD.MethodsWe searched PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Clinical Trials from inception to 7 March 2022 to identify all randomized controlled trials (RCTs) of nilotinib reporting outcomes of interest in patients with PD. Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…It is increasingly acknowledged that certain OACDs may be effective against neurodegenerative and autoimmune diseases [ 9 , 108 ]. Nilotinib, a BCR-ABL tyrosine kinase inhibitor, has been investigated in multiple cases as a medication against mental disorders, such as Parkinson’s disease and Alzheimer’s disease [ 109 , 110 ]. The rationale of these indications is that nilotinib leads to the degradation of misfolded α-synuclein by autophagy [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly acknowledged that certain OACDs may be effective against neurodegenerative and autoimmune diseases [ 9 , 108 ]. Nilotinib, a BCR-ABL tyrosine kinase inhibitor, has been investigated in multiple cases as a medication against mental disorders, such as Parkinson’s disease and Alzheimer’s disease [ 109 , 110 ]. The rationale of these indications is that nilotinib leads to the degradation of misfolded α-synuclein by autophagy [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tested on clinical phase I and phase II studies, it proves its safety and tolerability, with no adverse effects observed and a decrease in oligomeric forms of the α-syn in PD patients [198,199]. However, a recent meta-analysis concluded that it had no effect on motor outcomes [200]. Pagan and colleagues support starting a phase 3 trial project to evaluate nilotinib 300 mg in a more extensive multicenter study [199].…”
Section: Drugs Currently In Clinical Trialsmentioning
confidence: 99%
“…A meta-analysis of fMRI research on cognitively impaired PD patients indicates that cognitive dysfunction in PD is related to decreased connectivity within cognitive-related networks, with the most prominent effect observed in the default mode network (DMN) [31]. Another fMRI meta-analysis revealed a series of brain perfusion and regional functional abnormalities in PD, which are predominantly centered around brain regions related to the striato-thalamo-cortical circuits, are associated with the clinical manifestations of patients with PD [32]. MRI-based assessment of brain gray matter volume is considered as an effective method to diagnose PD and to evaluate its progression.…”
Section: Introductionmentioning
confidence: 99%